Information processing in freight and freight forward markets: An event study on OPEC announcements - Philipp Lauenstein; André Küster Simic (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
In this paper, information processing in spot and forward freight markets with respect to the Organization of the Petroleum Exporting Countries (OPEC) output announcements is investigated. We use the event study methodology to study returns in tanker freight spot and forward markets around OPEC conferences from 2003 to 2014. Significant abnormal returns indicate that the output decisions are informationally important for the pricing of crude oil transportation services. We consistently find patterns of positive abnormal returns around production increase announcements and negative abnormal returns around announcements of production cuts. Our analysis also suggests that market participants appear to trade three to five days prior to the final announcement based on their anticipation of the actual output announcements. This is consistent with findings from related studies on crude oil returns. Persistence of abnormal returns in the post-event period indicates incomplete initial reactions or at least slow adjustment to disseminated information.
Keywords: F10; G13; G14; 330; Tanker Freight Rates; Freight Forwards; OPEC; Informational Efficiency; Event Study